2016
DOI: 10.1111/rec.12455
|View full text |Cite
|
Sign up to set email alerts
|

Hardwood management and restoration of longleaf pine ecosystems may affect raccoon daytime resting sites

Abstract: Fire‐maintained Pinus palustris (longleaf pine) ecosystems are species rich and considered a top conservation priority in the southeastern United States. Ground‐nesting species such as Gopherus polyphemus (gopher tortoise) and Colinus virginianus (northern bobwhite) thrive in longleaf ecosystems. However, the generalist carnivore Procyon lotor (raccoon) is a significant predator of these endemic ground nesters. In forested ecosystems, raccoons prefer hardwood‐dominated habitats. Removal of hardwood trees, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…Nonetheless, the majority of Seminole bat, and all of the hoary bat day-roosts we found were located in mesic areas with longer fire return intervals rather than in the larger xeric landscape with plantations or natural pine. The importance of these mesic areas and pine-hardwood mixed forests, as well as fire regimes, have been previously noted across a suite of different taxa [73,74], including at CB [75]. Our result finding that bats select more for mesic habitat in areas of less frequent fires supports the hypothesis that roost selection may be a function of seeking to minimize mortality risk from fire caused evacuations.…”
Section: Plos Onesupporting
confidence: 86%
“…Nonetheless, the majority of Seminole bat, and all of the hoary bat day-roosts we found were located in mesic areas with longer fire return intervals rather than in the larger xeric landscape with plantations or natural pine. The importance of these mesic areas and pine-hardwood mixed forests, as well as fire regimes, have been previously noted across a suite of different taxa [73,74], including at CB [75]. Our result finding that bats select more for mesic habitat in areas of less frequent fires supports the hypothesis that roost selection may be a function of seeking to minimize mortality risk from fire caused evacuations.…”
Section: Plos Onesupporting
confidence: 86%
“…Chamberlain and Leopold [ 9 ] found suggested that removal of hardwoods in these forests may be detrimental to gray fox populations. Removal of mature hardwoods from within the longleaf pine matrix [ 55 ], [ 56 ] occurred since the Temple et al [ 10 ] study and this removal may be the reason for reduced gray fox use of the property. Similarly, hardwood removal resulted in reduced use by raccoons [ 55 ] suggesting hardwood removal from within pine dominated forests may be an alternative to traditional lethal control in limiting nest predation within this forest type.…”
Section: Discussionmentioning
confidence: 99%
“…As with raccoons [ 55 ], [ 65 ], some [ 66 ] have suggested that gray foxes rest in trees, but limited evidence exists for such behavior [ 67 ]. We found no evidence of gray foxes diurnally resting in trees, yet they were often found in areas with low, sprawling branches that may facilitate climbing, and gray foxes may have climbed these trees to flee predators.…”
Section: Discussionmentioning
confidence: 99%
“…3). We predicted depredations by raccoons would decrease (Kirby et al 2016 a , b ), but we did not detect raccoons at Bachman's Sparrow nests, despite their prevalence as a nest predator across studies, species, and locals (DeGregorio et al 2014) and their presence and activity at our study sites (Malone 2019; Tall Timbers, unpublished data ). The relationship between Bachman's Sparrow nests and recent fires may explain this result, as they prefer nest sites burned within the last 12 months (Jones et al 2013) and raccoons are less likely to forage in these areas (Jones et al 2004).…”
Section: Discussionmentioning
confidence: 55%
“…In turn, hardwood reduction in pine savanna is considered a means to alter the community of adult and nest predators via changes in habitat use by predators or prey (Whittingham and Evans 2004, Kirby et al 2016 a , Jacques et al 2017, Stevenson et al 2018). Indeed, habitat management can be used to reduce predation by either increasing cover for prey (Schranck 1972), reducing breeding or perching sites for predators (Gibbons 2007, Kirby et al 2016 b ), reducing edge habitat used by predators (Chalfoun and Martin 2009, Ellison et al 2013), or increasing food resources for prey (Martin 1993). Predator responses to manipulations of habitat structure can include both functional (e.g., altered foraging patterns) or numerical shifts (e.g., emigration to higher quality habitat; Klug et al 2010, Kirby et al 2016 a ).…”
Section: Introductionmentioning
confidence: 99%